A comparative study on radio frequency identification system and its various applications - Muhammad Baballe Ahmad; Fatima Alkasim Nababa (Institute of Advanced Engineering and Science, 2021)
The radio frequency identification (RFID), is a wireless technology system that is used for identifying an individual or objects through the means of radio waves that transfer information from an electronic tag, called an RFID tag. RFID consists of two main components the interrogator and the transponder. The Interrogator, which is the RFID reader, the interrogator usually transmits and receives the signal while the transponder that is the tag, is attached to the object. In the RFID system, an RFID reader interrogates the RFID tags. This tag reader generates a radio frequency interrogation, which communicates with the tags been registered in the system. This reader likewise has a receiver that captures a reply signal generated from the tags and decodes the signal. This reply signal from the tags reflects the tag's information content. Each tag of the employee or student consists of a unique identity, identification card (ID) that is assigned to a single employee or student ID card, which is recorded, in the database of the system. This research reviews some recent designs and implementation of internet of things (IoT) attendance systems using the concept of the RFID system. The analysis found that the RFID system is a very advanced technology for an automatic attendance system in an institution, organization or university, and it provides a very higher performance and accuracy than the traditional paper-based system that the employees or students normally used to sign. The use of the RFID technology enables the institution, authorities, or management to evade attendance documents from damages such as misplacement, tear, or even got lost. A combination of the model is needed which will confirm higher security, better performance, and consistency of the system.